APLIKASI PEMBELAJARAN AL-QUR’AN DALAM KAJIAN ILMU TAHSIN BERBASIS MULTIMEDIA - Dadi Rosadi; Ali Mulyawan (STMIK Mardira Indonesia, Bandung, 2021)
The law of learning tahsin science or what is known among the public as tajwid science is fardhu kifayah, while reading the Al-Qur'an with tahsin science is wajib'ain, meaning that a Muslim, male or female, must read the Al-Qur'an with tahsin knowledge, if If not, then he is a sinner because the reading may violate the meaning if he is wrong in pronouncing it. This application displays the main content of reading the Al-Qur'an, the etiquette of reading the Al-Qur'an, and the study of the science of tahsin as a whole such as the law of reading, the introduction of gharibah (foreign) verses, how to waqof (stop) and recognize common mistakes that often occur. while reading the Al-Qur'an. To produce an application for the introduction of tahsin learning by utilizing mobile web-based smartphone technology, especially smartphones with the Android operating system. With the existence of a tahsin learning application developed by utilizing mobile technology, it is expected to be able to help provide solutions for a Muslim who wants to learn to improve and improve the reading of the Al-Qur'an without being bound by time and can learn to read the Al-Qur'an in accordance with the guidance of the Sunnah of the Rasulullah Shallallahu ‘alaihi wasallam. Keywords: Tahsin Science, Tajweed Law, Android Mobile, Mobile WEB.DOI : 10.5281/zenodo.5784114